PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP FREE CASH FLOW DAN STRUKTUR MODAL PERUSAHAAN CONSUMER GOODS DI BURSA EFEK INDONESIA - Sukanti, Ni Ketut; Wiagustini, Ni Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2015)
The main objective of a company is to maximize wealth for its shareholders. Company owners or shareholders cannot manage his own company; therefore the owner hires another party as a manager who will perform the activities of corporate management. Manager on behalf of the owner of the company will make important decisions relating to company operations. One of the decisions taken by the manager is a corporate finance decision. Managers are required to be able to increase the value of the company or the owner of the company (shareholders) to maximize wealth. In fact, managers tend to prioritize their personal interests. This study aims to determine the effect of institutional ownership and free cash flow to the capital structure. Institutional ownership is a proportion of shares held by institutions. Free Cash Flow (FCF) is the cash flow available for distribution to investors after the company made investments in fixed assets and working capital necessary to sustain business continuity. Capital structure is the composition of the sources of internal funds and external sources of funds managed by a company. The population in this study was all of the sub sectors of consumer goods companies' in the Indonesian stock exchange. Testing the hypothesis of the study used path analysis techniques with the application tool of SPSS (Statistical Product and Service Solutions). The results showed that 1) Institutional ownership has a positive and significant impact on Free Cash Flow. 2) Institutional ownership has a significant and positive effect on capital structure. 3) Free Cash Flow has a significant negative effect on capital structure. The higher institutional ownership is capable of influencing the increase in Free Cash Flow of Consumer Goods Companies in the Indonesian Stock Exchange. The higher institutional ownership is capable of influencing the increased use of debt in the Consumer Goods Companies in Indonesia Stock Exchange. Free Cash Flow is not able to influence the higher increase in the use of debt of Consumer Goods Companies in Indonesia Stock Exchange.
Keywords: Institutional ownership, free cash flow and capital structure.